Properties of hot and dense matter from relativistic heavy ion collisions - Braun-Munzinger, Peter; Koch, Volker; Schäfer, Thomas; Stachel, Johanna (Physics reports, 2016)
We review the progress achieved in extracting the properties of hot and dense matter from relativistic heavy ion collisions at the relativistic heavy ion collider (RHIC) at Brookhaven National Laboratory and the large hadron collider (LHC) at CERN. We focus on bulk properties of the medium, in particular the evidence for thermalization, aspects of the equation of state, transport properties, as well as fluctuations and correlations. We also discuss the in-medium properties of hadrons with light and heavy quarks, and measurements of dileptons and quarkonia. This review is dedicated to the memory of Gerald E. Brown.
Gesehen am 19.05.2020